2021
DOI: 10.14503/thij-20-7446
|View full text |Cite
|
Sign up to set email alerts
|

Atypical ST-Segment-Elevation Myocardial Infarction Presentation in Patients With COVID-19 at a High-Volume Center in New York City

Abstract: Atypical presentations of ST-segment-elevation myocardial infarction (STEMI) have been reported in patients who have COVID-19. We have seen this occurrence in our center in Bronx, New York, where multitudes of patients sought treatment for the coronavirus. We studied the prevalence of atypical STEMI findings among patients with COVID-19 who presented during the first 2 months of the pandemic. Consistent with previous reports, 4 of our 10 patients with COVID-19 and STEMI had no identifiable culpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Equally quickly, a different course of STEMI in the course of SARS-CoV2 infection began to be observed. It was found that some of the infected patients undergoing invasive examination did not have an identifiable coronary lesion [ 12 ], and the occurrence of non-obstructive coronary artery disease was significantly more frequently observed in COVID-19 STEMI than in the control group (13% vs. 1%, p = 0.03) [ 13 ]. In addition, there have been reports that this problem occurred with an increased frequency in women (1/3 of women vs. 1/5 of men) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equally quickly, a different course of STEMI in the course of SARS-CoV2 infection began to be observed. It was found that some of the infected patients undergoing invasive examination did not have an identifiable coronary lesion [ 12 ], and the occurrence of non-obstructive coronary artery disease was significantly more frequently observed in COVID-19 STEMI than in the control group (13% vs. 1%, p = 0.03) [ 13 ]. In addition, there have been reports that this problem occurred with an increased frequency in women (1/3 of women vs. 1/5 of men) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…De novo hypercoagulability, resulting in vessel thrombosis and occasional patchy ischemic damage to multiple parenchymal tissues ( 9 , 12 , 13 , 15 17 , 22 , 26 , 28 , 29 );…”
Section: The Heart In Covid-19mentioning
confidence: 99%
“…Acute myocardial infarction (AMI), although generally rare, is caused by epicardial coronary artery thrombosis (probably induced by sudden progression of preexisting unstable, atherosclerotic soft plaques activated by systemic inflammation, hypercoagulable state, endothelial damage, or hypertensive spells) ( 29 , 33 ). Localized segmental hypokinesia (more than 1 cm 2 in echocardiographic area) correlates with ECG changes and, although rare, makes a strong clinical case for AMI ( 26 ).…”
Section: The Heart In Covid-19mentioning
confidence: 99%